Peran Literasi Keuangan dan Kontrol Diri terhadap Minat Menabung Mahasiswa dalam Perspektif Theory of Planned Behavior - Saverius Kebabu; Andri Paulus Loe; Fernando Saragih (Varied Knowledge Journal, 2026)
This study focuses on the process of the formation of variable Y through the influence of the independent variables, specifically X1 and X2, involving students as the research subjects. In addition, this study also considers respondents’ characteristics, such as gender, economic background, and place of residence. The purpose of this research is to identify the effects of financial literacy and self-control ability on the saving interest of students from the Faculty of Teacher Training and Education at Universitas Nusa Cendana by considering the criteria mentioned above. This research adopts a quantitative approach with an explanatory research design. The sample consisted of 100 students selected using incidental nonprobability sampling techniques. Data were collected through questionnaires that had been tested for validity and reliability. The analytical techniques employed included multiple linear regression, t-tests, F-tests, and the coefficient of determination, after all classical assumption tests had been fulfilled. The results of this study indicate that financial literacy has a positive and significant effect on saving interest, with a t-value of 22.899. Self-control ability also demonstrates a positive and significant influence, with a t-value of 22.871. Simultaneously, both variables have a significant effect on saving interest, with an F-value of 626.207 and a significance level of 0.000. The coefficient of determination value of 92.8% indicates that saving interest is influenced by financial literacy and self-control, while the remaining percentage is affected by other factors outside the scope of this study.